2019
DOI: 10.3847/1538-4357/ab09f7
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Strength of Porous Dust Aggregates

Abstract: Comets are thought to have information about the formation process of our solar system. Recently, detailed information about comet 67P/Churyumov-Gerasimenko has been found by a spacecraft mission Rosetta. It is remarkable that its tensile strength was estimated. In this paper, we measure and formulate the tensile strength of porous dust aggregates using numerical simulations, motivated by porous dust aggregation model of planetesimal formation. We perform three-dimensional numerical simulations using a monomer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 40 publications
2
50
0
Order By: Relevance
“…To close this section, it is important to mention that the results of Musiolik & Wurm (2019) have been regarded as controversial by some authors. Garcia & Gonzalez (2020) point out that the results of Musiolik & Wurm (2019) disagree with the tensile strength computed numerically by Tatsuuma et al (2019). Okuzumi & Tazaki (2019) mention that Musiolik's recent experiments are inconsistent with earlier ones performed by Gundlach & Blum (2015), which showed efficient sticking of H 2 O grains for temperatures down to 100 K. In addition, missing key aspects such as porosity (Garcia & Gonzalez 2020;Krijt et al 2016) and the lack of experiments involving mixtures of silicates and ices (Choukroun et al 2020) Fig.…”
Section: Appendix A: Dependence On the Fragmentation Velocity Of Grainsmentioning
confidence: 84%
“…To close this section, it is important to mention that the results of Musiolik & Wurm (2019) have been regarded as controversial by some authors. Garcia & Gonzalez (2020) point out that the results of Musiolik & Wurm (2019) disagree with the tensile strength computed numerically by Tatsuuma et al (2019). Okuzumi & Tazaki (2019) mention that Musiolik's recent experiments are inconsistent with earlier ones performed by Gundlach & Blum (2015), which showed efficient sticking of H 2 O grains for temperatures down to 100 K. In addition, missing key aspects such as porosity (Garcia & Gonzalez 2020;Krijt et al 2016) and the lack of experiments involving mixtures of silicates and ices (Choukroun et al 2020) Fig.…”
Section: Appendix A: Dependence On the Fragmentation Velocity Of Grainsmentioning
confidence: 84%
“…Based on the OSIRIS images, the tensile strength of comet 67P is estimated (Groussin et al 2015;Basilevsky et al 2016). Recently, Tatsuuma et al (2019) studied the tensile strength of dust aggregates and found that the tensile strength of comet 67P is reproduced when the monomer radius is between 3.3 − 220 µm. Hence, sub-millimeter-sized solid spheres are candidates to explain the measured tensile strength.…”
Section: Comparison With Cometary Dust In the Solar Systemmentioning
confidence: 99%
“…As an example model, adopting a simple size dependence on the tensile strength normalization ofσ = (a eff /1 µm) −3 results in a smooth transition fromσ = 15 for the 0.4 µm case toσ = 0.6 for the 1.2 µm case. For comparison, the size-dependent tensile strength of micron-to-millimeter-scale aggregates follows, according to numerical simulations (Tatsuuma 2019), aσ = (a eff /1 µm) −2 law. The example model overestimates tensile strengths given by both the microcrack theory and numerical simulations of aggregates, as the smallest particles are composed of two monomers.…”
Section: Spectral Bluing By Disruption Processesmentioning
confidence: 98%